2012
DOI: 10.1254/jphs.12058fp
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clonidine on Renal Sodium Handling in Spontaneously Hypertensive Rats

Abstract: Abstract. Up-regulation of kidney α 2 -adrenoceptor expression has been implicated in the development of hypertension in spontaneously hypertensive rats (SHR). This study was carried out to evaluate renal sodium excretion in response to clonidine administration in SHR and control normotensive Wistar-Kyoto (WKY) rats. SHR and WKY rats (12-week-old) were placed in metabolic cages for 4 days: the first 2 days in control conditions and the following 2 days under oral clonidine treatment (100 μg/kg body weight). Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Furthermore, a previous study using isolated perfused kidneys from SHRs revealed an intrinsic renal abnormality in sodium excretion that may contribute to the maintenance of hypertension in SHR ( 25 ). Renal sympathetic nerves and circulating catecholamine are involved in the regulation of sodium and water excretion in the kidney ( 26 ). In the present study, a significant change to sodium excretion was observed following RD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a previous study using isolated perfused kidneys from SHRs revealed an intrinsic renal abnormality in sodium excretion that may contribute to the maintenance of hypertension in SHR ( 25 ). Renal sympathetic nerves and circulating catecholamine are involved in the regulation of sodium and water excretion in the kidney ( 26 ). In the present study, a significant change to sodium excretion was observed following RD.…”
Section: Discussionmentioning
confidence: 99%
“…The assay of l ‐DOPA, monoamines (DA and noradrenaline) and DA metabolites (DOPAC, HVA and 3‐MT) in urine samples was performed by means of high‐performance liquid chromatography with electrochemical detection, as previously described . In brief, aliquots of 5 μl of acidified urine were placed in 5‐ml conical‐based glass vials with 50 mg alumina, and the pH of the samples was adjusted to pH 8.6 by the addition of Tris buffer.…”
Section: Methodsmentioning
confidence: 99%